1996
DOI: 10.1073/pnas.93.1.91
|View full text |Cite
|
Sign up to set email alerts
|

Yeast actin: polymerization kinetic studies of wild type and a poorly polymerizing mutant.

Abstract: Wild-type actin and a mutant actin were isolated from yeast (Saccharomyces cerevisiae) and the polymerization properties were examined at pH 8.0 and 20°C. The polymerization reaction was followed either by an increase in pyrene-labeled actin fluorescence or by a decrease in intrinsic fluorescence in the absence of pyrene-labeled actin. While similar to the properties of skeletal muscle actin, there are several important differences between the wild-type yeast and muscle actins. First, yeast actin polymerizes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 30 publications
5
43
1
Order By: Relevance
“…Previous studies have shown that addition of a N-terminal His tag to yeast actin does not affect its polymerization or function in yeast (Buzan and Frieden, 1996;Buzan et al, 1999). Nevertheless, we tested whether the presence of the N-terminal tag affected polymerization of TgACT1 by mon-itoring the quenching of tryptophan fluorescence, which is an inherent property of actins.…”
Section: Polymerization Kinetics Of Tgact1mentioning
confidence: 99%
“…Previous studies have shown that addition of a N-terminal His tag to yeast actin does not affect its polymerization or function in yeast (Buzan and Frieden, 1996;Buzan et al, 1999). Nevertheless, we tested whether the presence of the N-terminal tag affected polymerization of TgACT1 by mon-itoring the quenching of tryptophan fluorescence, which is an inherent property of actins.…”
Section: Polymerization Kinetics Of Tgact1mentioning
confidence: 99%
“…Yeast, compared with muscle actin, polymerizes faster and exchanges its bound nucleotide faster. In contrast to muscle actin, the yeast actin filament releases its P i almost immediately after ATP hydrolysis and the filament fragments more readily (4). Yeast cells cannot survive with muscle actin as the sole actin, and with ␤-nonmuscle actin as the only actin, yeast cells are very sick (5).…”
mentioning
confidence: 99%
“…It has long been appreciated that actin is a highly dynamic protein [Buzan and Frieden, 1996;Kim et al, 1996], and that allostery plays a major role in actin function based on the fact that alterations in actin structure can exert long-distance effects through the protein [McKane et al, 2005[McKane et al, , 2006. Supporting evidence lies in the fact that modification of the actin C-terminus by proteolysis, antibody binding and by mutagenesis can significantly impact actin polymerization properties [Johannes and Gallwitz, 1991;Crosbie et al, 1994;Orlova and Egelman, 1995;Phan et al 1997;Hegyi et al, 1998;Kim et al, 1998].…”
Section: Budding Yeast As An Expression System For Mutant Actinsmentioning
confidence: 89%